Empowering Women through Language and Technology: A Study on Women’s Participation in Education in the Digital Era - Kushieva Nodira Khabibjonovna; Bushra Sumaya (Women, Education, and Social Welfare, 2025)
Women’s education has become one of the most essential dimensions of sustainable development in the digital age. This study explores how technology and language education empower women, focusing on their participation, challenges, and achievements in higher education contexts. Using a mixed-methods approach with survey data (n=420) and in-depth interviews (n=25) from female students and educators in Uzbekistan’s universities, the study identifies key enabling and limiting factors in women’s engagement in language and technology-based education. Results reveal that access to digital tools, supportive learning environments, and English language proficiency significantly increase self-efficacy, employability, and academic motivation among women. The study also finds that socio-cultural barriers, digital inequality, and traditional perceptions of gender roles remain major obstacles. The discussion highlights the role of educational institutions, language pedagogy, and technological empowerment in bridging gender gaps. Recommendations include integrating digital literacy into language curricula, promoting mentorship, and creating gender-sensitive online learning platforms.